The Great Clock Tower: Time and Narrative in the Late Works of W.B. Yeats - SCANLON, JAMES (Trinity College Dublin. School of English. Discipline of English, 2018)
James Scanlon The Great Clock Tower: Time and Narrative in the Late Works of W.B. Yeats This dissertation is a study of time and narrative in the late works of W.B. Yeats. I argue that, in the early twentieth century, the problem of time was made visible in new ways, as the nature of time, and even the reality of time, became the subject of debate among physicists and philosophers. The element of narrative is introduced by way of the philosophy of Paul Ricoeur. In his study of the ways in which narrative makes productive the aporia between physical and phenomenological time, Ricoeur looked at narrative structure in works by Thomas Mann, Virginia Woolf, and Marcel Proust. This dissertation is an attempt to apply the same approach, close analysis of narrative structures, to the late works of W.B. Yeats. Yeats?s work is suitable for this type of study because, as described in Chapter 1, he used one of his most ambitious texts, A Vision (1925 and 1937), to re-imagine the secret workings of time. I argue that Yeats was attempting to produce a unified theory that would apply to the small scale of the individual life and the larger scale of human history. As finally revealed, it would be the ?great clock tower?. In the remaining chapters, I trace some of the ways in which Yeats experimented with narrative form as part of his exploration of temporality. I have deliberately selected texts from different genres because I want to demonstrate the extent to which formal constraint and generic expectation permits or inhibits the evolution of narrative, particularly narrative that tries to depict non-linear time. Accordingly, Chapter 2 is largely concerned with autobiography, Chapter 3 with lyric, and Chapter 4 with stage drama. On the issue of chronology, the selection of texts allows the dissertation to follow its own winding path. Accordingly, Chapter 1 is concerned with texts that appear in 1925 and 1937 respectively. Chapter 2 then jumps back to 1921-1922, with the publication of The Trembling of the Veil. Chapter 3, which is concerned with the poetry of The Tower (1928) and The Winding Stair (1933) traces a path between the two Visions. Finally, Chapter 4 moves beyond the second version of A Vision, to the first production of Purgatory on 10 August 1938 at the Abbey Theatre. In each chapter, I try to bring Yeats?s narrative structures to light, and to demonstrate the extent to which it is possible to trace characteristic techniques and devices, such as, for example, the way in which narrative is reversed or the way in which two separate narratives, moving in opposite directions, might co-exist in a single text. The methodology that I follow is a simple form of structuralism, after the practical example of critics like Frank Kermode, with theoretical support from Jonathan Culler. This approach is joined to close reading, following the example of critics like Helen Vendler and Nicholas Grene. The combination of both approaches has helped me to see where Yeats?s model of time might be embedded at different levels of discourse, from word and sentence to text and volume.
Time and Narrative in the Late Works of W.B. Yeats
APPROVED
Keywords: Time; Yeats; Narrative; Genre